Performance analysis of peel test on fused filament fabricated polypropylene-aluminium. (2021) - Sahayaraj, A. Felix; Kannan, N. Senthil; Girisha, L.; Kannan, S.; Rahul, D.; Subbiah, Ram
Highlights: Polypropylene is added to the aluminum 6061 alloy through fused filament fabrication technique. The adhesive strength between polypropylene and aluminium 6061 is evaluated through peel test. Polypropylene is added to the aluminum 6061 alloy through fused filament fabrication technique. The adhesive strength between polypropylene and aluminium 6061 is evaluated through peel test. Abstract: Fused filament fabrication is played a crucial role in manufacture of components with high quality. In additive manufacturing, fused filament fabrication (FFF) is an effective method to fabricate metal and non metals. Polypropylene (PP) consists of more gorgeous substance properties. It is a rigid and crystalline thermoplastic material. It is added to the aluminium 6061 alloy through fused filament fabrication technique. The adhesive strength between polypropylene and aluminium 6061 is evaluated through peel test. The adhesive strength is depends on the control factors such as peel angle, speed and peeling force. The desirable adhesive strength is analyzed by signal to noise ratio which is derived from Taguchi method. The involvement of each factor on peel strength or adhesive strength can be determined through variance analysis.